Development of environmentally friendly bio-epoxy coatings for water-repellent applications - Bellido Aguilar, Daniel Angel (Nanyang Technological University, 2021)
Hydrophobic coatings are made of materials that have low affinity to water. Driven by their water-repellent properties, hydrophobic coatings are envisioned to be employed as anti-icing and anti-corrosion coatings. Epoxy coatings, one of the most important thermosets, are commonly hydrophilic, and, therefore, preparing hydrophobic films from hydrophilic epoxy resins is a scientific challenge. Despite of the great achievements in preparing hydrophobic epoxy films with good performance, the preparation of hydrophobic epoxy coatings still faces two serious problems. First, the epoxy resins commonly used are derived from Bisphenol A, which is an organic compound produced from petroleum sources and has been found to be an endocrine disrupting chemical. Second, the synthesis procedures involve the use organic solvents or small organic compounds that are released into the air. In other words, current hydrophobic epoxy coatings are not environmentally friendly synthesized. Therefore, the ultimate aim of this research is to prepare hydrophobic coatings with epoxy resins obtained from biomass precursors without requiring the use of organic solvents during the film preparation. The developed bio-based coatings are examined for the anti-icing and anti-corrosion performances. Three different epoxy polymer formulations were developed based on isosorbide, cardanol and glycerol. The bio-based contents of the polymer formulations were progressively increased by incorporating bio-based curing agents and hydrophobizers. Furthermore, the hydrophobization of the bio-based epoxy polymers was achieved to different degrees by the incorporation of various hydrophobizers. In addition, the wettability, thermal and mechanical properties of the bio-based thermosets were studied. The anti-icing and anti-corrosion performances of the epoxy coatings were also evaluated in relation with the bulk and surface properties of the coatings. The overall results of this research have demonstrated that coatings with hydrophobic coatings for water-repellent applications can be prepared from bio-based compounds with tunable properties according to the selected compounds and employed synthesis method. Therefore, this research contributes to the development of green epoxy coatings for water-repellent applications. Finally, future work is suggested for the continuation and enrichment of this research.